Genome expression analysis of basic helix-loop-helix transcription factors in Sea buckthorn (Hippophae rhamnoides L.) - Zhang, Jiajia; Du, Gaigai; Zhang, Guoyun; Zhang, Jianguo; Diao, Songfeng (Frontiers in Plant Science, 2024)
The basic helix-loop-helix (bHLH) transcription factor family is one of the largest gene families in plants, extensively involved in plant growth, organ development, and stress responses. However, limited studies of this family are available in sea buckthorn (Hippophae rhamnoides). In this study, we identified 144 bHLH genes in H. rhamnoides (HrbHLH) through a genome-wide search method, then explored their DNA and protein sequences and physicochemical properties. According to the sequence similarities, we classified them into 15 groups with specific motif structures. To explore their expressions, we performed gene expression profiling using RNA-Seq and identified 122 HrbHLH mRNAs were highly expressed, while the remaining 22 HrbHLH genes were expressed at very low levels in all 21 samples. Among these HrbHLH genes, HrbHLH47, HrbHLH74, HrbHLH90, HrbHLH131 showed the highest expression level in the root nodule, root, leaf, stem and fruit tissues. Furthermore, eleven HrbHLH genes displayed increased expressions during the fruit development process of sea buckthorn. Finally, we validated the expression patterns of HrbHLH genes using reverse transcription quantitative real-time PCR (QPCR). This comprehensive analysis provides a useful resource that enables further investigation of the physiological roles and molecular functions of the HrbHLH TFs.